An implementation of Hill cipher and 3x3x3 rubik's cube to enhance communication security - Nana, Nana; Prasetyo, Puguh Wahyu (Universitas Ahmad Dahlan, 2021)
Message security is must be managed seriously. Therefore, to maintain the confidentiality of any message, cryptography is needed. Cryptography is a science that uses mathematics to encrypt and decrypt messages. Cryptography is used as a tool to protect messages, for example, national secrets and strategies.Â The method of this research is qualitative research with a literature review. This research implements a hybrid cryptographic algorithm by combining Hill cipher and 3x3x3 Rubik's cube methods with Python software simulation.